Islam as a Research Object - Muhammad Nur Kholis; Siti Ma’rufah; Anis Fitria; Damanhuri (al-Afkar, Journal For Islamic Studies, 2024)
Islamic education is indeed very interesting to study in more depth and education cannot be separated from the nature of education itself. In studying Islamic education, humans need an understanding of issues of Islamic science and religion. Ananta Wijaya in his book believes that science and religion are two different entities. Both have different ways of working even though they were both born from the same point. Islamic education is defined as education with a universal paradigm, in this context it is humans who dedicate themselves as caliphs on earth. This research aims to analyze the Islamic religion related to Islamic educational research with all the aspects that make it up. The research method used is Literature Review. Based on the results of research, religion is not born from testing whose quality of truth is very subjective. Religion means a bond that must be adhered to and obeyed by humans. Religion is an absolute element in developing personal character and building a harmonious and peaceful social life, educating them to have a calm soul, dare to uphold the truth, have commendable morals and be able to elevate human status higher than other creatures of God. Human needs for religion are based on several dominant factors, namely natural factors, human shortcomings and weaknesses and the challenges they face. Therefore religion is a very complete package needed by humans.